(untitled) (Islamic Sciences Journal, 2023)
The Arabic speech is considered one of the literary arts that stemmed responding for the human nature to express himself , his ideas and opinions. This arts developed across the eras due to certain changes, until it reached into the prosperous stages during the first Abbasid era. This paper studies the political speech in this era. It defines the art of speech linguistically and idiomatically, it also shows how this art developed from the pre-Islamic era until the first Abbasid era. This paper also analyzes the two political speech during the first Abbasid era, it explains its categories, subjects, and significance during that era. It also shows the eloquence of the Abbasid Caliphs by mentioning same phenomenon of the eloquence and how they grow up in a literary and linguistically forms. Finally, the researcher analyzes two samples of political speech of (Abu Ja’afir Al-Mansour) and (Al-Maa’amoon) and elicits the artistic features of the political speech during the Abbasid era.